Candida coinfection among patients with pulmonary tuberculosis in Asia and Africa; A systematic review and meta-analysis of cross-sectional studies. (February 2020) - Hadadi‐Fishani, Mehdi; Shakerimoghaddam, Ali; Khaledi, Azad
Abstract: Diagnosis of fungal co-infections in patients suffering from pulmonary tuberculosis has critical importance. Therefore, we aimed to determine the prevalence of candida coinfection in patients with pulmonary tuberculosis. The present systematic review of cross-sectional studies was conducted based on the Preferred Reporting Items for Systematic reviews and Meta-analysis (PRISMA) Protocol. Studies published online in English from January 2001 to March 2019 were assessed. Literature search was done in Web of Science, MEDLINE/PubMed, and Scopus databases and search engines using keywords combinations of "pulmonary fungi", "pulmonary coinfection", OR "pulmonary mycosis", "pulmonary fungal infections/agents", OR "polymicrobial infection", OR "secondary infection", OR "mixed infections", "pulmonary candidiasis", "fungi coinfection", "fungal co-colonization", AND "pulmonary tuberculosis", OR "pulmonary TB", AND "Asia", AND "Africa". Data was analyzed using Comprehensive Meta-Analysis software (CMA). Heterogeneity between studies was evaluated by Cochran's Q and I 2 tests. The pooled prevalence of candida coinfection among patients with pulmonary tuberculosis was 25.7% (95% CI: 23.7–27.9). C. albicans was the most prevalent Candida spp . with a pooled prevalence of 65.8% (95% CI: 54.3–75.7). Risk factors of candida coinfection were smoking, diabetes, advanced age, and low body mass index. The present review showed a high rate of candida coinfection among patients suffering from pulmonary tuberculosis. So, appropriate measures are necessary to early diagnose and treat these infections. Highlights: The pooled prevalence of candida coinfection among patients with pulmonary tuberculosis was 25.7% (95% CI: 23.7–27.9). C. albicans was the most prevalent Candida spp . with a pooled prevalence of 65.8% (95% CI: 54.3–75.7). Risk factors of candida coinfection were smoking, diabetes, advanced age, and low body mass index.